The Social Context of Organized Nonbelief: County-Level Predictors of Nonbeliever Organizations in the United States - García, Alfredo (Journal for the scientific study of religion, 2016)
Many recent social scientific studies have noted that the percentage of Americans with no religious affiliation is on the rise, but few have examined the nonbeliever organizations that some of these nones might join. This study uses an original data set, the first attempt at documenting the population of local nonbeliever organizations in the United States, to explore where these groups are more likely to flourish. Though one might assume that less religious counties, as measured by the percentage of those with no stated religious affiliation, would be more likely to contain nonbeliever organizations, this article provides evidence that they emerge more frequently and in greater numbers in counties with proportionally more evangelical Protestants. The percentage of evangelicals among a county's population is strongly associated with both the existence (dichotomously coded) and the number of nonbeliever organizations, even when controlling for a range of demographic and institutional factors.